Strategic decision analysis to enhance labor productivity affected by sick leave absenteeism in the manufacturing industry - Riska Bagus Setyawan; Manahan Siallagan (LPPM STIE Krakatau, 2025)
Purpose: To analyze the effect of sick leave absenteeism on labor productivity in a manufacturing factory and recommend strategies to meet the 2% absenteeism target. Methodology/approach: Mixed qualitative–quantitative method using Kepner-Tregoe analysis, fishbone diagram, and prioritization matrix. Data came from attendance records, medical reports, interviews, FGDs, and secondary sources. Results/findings: Sick leave contributed 3.06% to a total absenteeism rate of 3.36% in 2022, exceeding the target. Key causes were lifestyle issues, unsafe work areas, financial motives, ergonomics, chemical exposure, and weather. Six priority solutions were set: validate sick notes, healthy condition competitions, strengthen safety culture, Kaizen for work improvements, provide PPE, and healthy lifestyle education. Conclusions: With a US9,050 budget, the six strategies can reduce absenteeism and improve productivity if monitored over six months. Limitations: Focused on one factory with 550 employees, limiting generalization. Contribution: Presents an integrated decision-making model for reducing absenteeism and boosting manufacturing productivity.